RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR THE DETERMINATION OF REMDESIVIR IN IV FORMULATION - Mukesh P. Ratnaparkhi; Avinash R. Tekadea
The overall effect of the SARS-CoV-2 virus, instigating COVID-19, has highlighted the urgent need for effective treatments. Remdesivir, the only FDA-approved antiviral for severe COVID-19 in adults and children, requires precise analytical methods for its pharmaceutical formulation. Current HPLC techniques exist, but there is a critical demand for more efficient and accurate approaches. The current study addresses this need by developing and validating a specific HPLC method for quantitative analysis in an IV dosage form for remdesivirs. Utilizing a C18 column with a 0.7 mL min- p1 (Bflow rate, the analysis was completed in 10 minutes with an isocratic mobile phase of 50:50 V/V acetonitrile and methanol. Validation followed ICH Q2 (R2) guidelines, confirming the method's suitability, linearity, precision, accuracy and robustness. The results indicate that this HPLC method is straightforward, efficient and highly sensitive, making it a valuable tool for ensuring the quality and efficacy of remdesivir.s